2019
DOI: 10.1111/jocs.14334
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid aortic valve repair with hemi‐remodeling technique and external ring annuloplasty

Abstract: Background: Current guidelines recommend root replacement when diameter of the sinuses of Valsalva are superior to 45 mm particularly for bicuspid valve. However, in case of tubular aorta aneurysms with moderate root dilatation (40-45 mm diameter), the approach is still debated regarding the increased risk of coronary reimplantation.We present a modified hemi-remodeling aortic repair technique that includes the replacement of the noncoronary sinus, ascending aorta, and valve repair with external ring annulopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…As reported by Wang et al [4][5][6] , residual AI has a poor prognosis often requiring aortic replacement or valvuloplasty, or aortic root replacement. Polos et al 7 performed a valve-sparing root reconstruction procedure(remodeling technique)for an SVA and Carlotta et al 8 conducted an aortic valve repair using a hemi-remodeling technique. However, Wingo et al 9 and Abraiov et al 10 reported in a retrospective study that good results can be obtained by patch closure or aneurysm plication.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Wang et al [4][5][6] , residual AI has a poor prognosis often requiring aortic replacement or valvuloplasty, or aortic root replacement. Polos et al 7 performed a valve-sparing root reconstruction procedure(remodeling technique)for an SVA and Carlotta et al 8 conducted an aortic valve repair using a hemi-remodeling technique. However, Wingo et al 9 and Abraiov et al 10 reported in a retrospective study that good results can be obtained by patch closure or aneurysm plication.…”
Section: Discussionmentioning
confidence: 99%
“…12 Another interesting recent modification that has demonstrated good medium-term patient outcomes in patients with a bicuspid valve and moderate aortic dilatation (40-45 mm) is the hemi-remodeling technique. 13 This method involves the replacement of the noncoronary sinus, ascending aorta, and valve repair with external ring annuloplasty. This technique avoids the operative risk of coronary reimplantation and allows better exposition on the valve for a symmetrical repair and allows shorter cross-clamp times.…”
Section: The First Aortic Root Replacement Was Demonstrated In 1968 Bmentioning
confidence: 99%
“…Annular stabilization modifications to the remodeling technique include the David III procedure which adds an external partial annuloplasty (PTFE strip at the base of the noncoronary sinus from trigone to trigone), 7 an external annuloplasty suture, 10 an external annuloplasty ring, 11 and an internal annuloplasty ring 12 . Another interesting recent modification that has demonstrated good medium‐term patient outcomes in patients with a bicuspid valve and moderate aortic dilatation (40–45 mm) is the hemi‐remodeling technique 13 . This method involves the replacement of the noncoronary sinus, ascending aorta, and valve repair with external ring annuloplasty.…”
mentioning
confidence: 99%
See 2 more Smart Citations